Routing in Wireless Multimedia Sensor Networks: A Survey of Existing Protocols and Open Research Issues - Vikas Bhandary; Amita Malik; Sanjay Kumar (Journal of Engineering)
With the advancement of wireless sensor networks (WSNs) and technology, applicability of WSNs as a system is touching new heights. The development of multimedia nodes has led to the creation of another intelligent distributed system, which can transfer real-time multimedia traffic, ubiquitously. Wireless multimedia sensor networks (WMSNs) are applicable in a wide range of areas including area monitoring and video surveillance. But due to unreliable error-prone communication medium and application specific quality of service (QoS) requirements, routing of real-time multimedia traffic in WMSNs poses a serious problem. The paper discusses various existing routing strategies in WMSNs, with their properties and limitations which lead to open research issues. Further, detailed classification and analytical comparison of discussed protocols are also presented.